Specific alterations of gut microbiota in patients with membranous nephropathy: A systematic review and meta-analysis - Zhang, Yumeng; Zhao, Jin; Qin, Yunlong; Wang, Yuwei; Yu, Zixian; Ning, Xiaoxuan; Sun, Shiren (Frontiers in Physiology, 2022)
Background: The pathogenesis of idiopathic membranous nephropathy (IMN) has not yet been thoroughly clarified, and gut dysbiosis may be a contributor to IMN. However, the characterization of gut microbiota in patients with IMN remains uncertain. Methods: Cochrane Library, PubMed, China National Knowledge Internet, Web of Science, and Embase were used to search for studies until February 21, 2022. A standardized mean difference (SMD) with 95% confidence interval (CI) based meta-analysis was conducted on the alpha diversity index. The between-group comparison of the relative abundance of gut microbiota taxa and beta diversity was extracted and qualitatively analyzed. Results: A total of five studies were included, involving 290 patients with IMN, 100 healthy controls (HCs), and 129 patients with diabetic kidney disease (DKD). The quantitative combination of alpha diversity indices indicated that although bacterial richness was impaired (Ace, SMD=0.12, [-0.28, 0.52], P = 0.55, I² = 0%; Chao1, SMD=-0.34, [-0.62, -0.06], P <0.05, I² = 36%), overall diversity was preserved (Shannon, SMD=-0.16, [-0.64, 0.31], P = 0.50, I² = 53%; Simpson, SMD=0.27, [-0.08, 0.61], P = 0.13, I² = 0%). The beta diversity was significantly varied compared to HCs or DKD. Compared to HCs, the abundance of Proteobacteria increased, while that of Firmicutes decreased at the phylum level. Furthermore, the amount of Lachnospira was depleted, while that of Streptococcus enriched at the genus level. Meanwhile, Proteobacteria and Streptococcus were also increased when compared with DKD patients. Conclusion: The expansion of Proteobacteria and depletion of Lachnospira may be critical features of the altered gut microbiota in patients with IMN, which may play an important role in the pathogenesis of IMN and can provide bacterial targets for diagnosis and therapy.